Formação continuada a partir do “chão da escola”: possibilidades e tensões de um processo participativo - Gai, Neli Aparecida (Universidade do Vale do Rio dos Sinos, 2015)
This thesis analyzes the experience of continuing education by literacy teachers, considering the proposal of Popular Education by the Education Network of the city of Chapecó (1994-2007). In the articulation between Popular Education Studies and Literacy and Continuing Education Studies, we have attempted to understand the processes of continuing education through the proposal of Popular Education, by analyzing the possibilities and tensions pointed out by a group of literacy teachers. The methodological approach adopted in this study has ethnographical inspiration. Records by the Education Department, such as the Journal of Popular Education, the Political-Pedagogical Project and documents produced in continuing education, such as the Area Record Book, have been analyzed. Besides, five literacy teachers that participated in continuing education in that period answered a questionnaire. For the analysis of the material, we used conceptual tools from Freirean studies: participation, emancipation and difference. With this theoretical-methodological support, we have advocated the thesis that a process of continuing education based on participation and collective work, by having Popular Education as a guide, is not enough to provide access to specific literacy knowledges. It is that both the university and the school, as well as other agencies in charge of education, such as the Departments of Education, develop educative practices with access to specific literacy knowledges as well as to the political and social dimensions of knowledge. Finally, we have discussed the relationships between the analyzed proposal and curriculum policies that have triggered it, in order to characterize improvements, hindrances, and the conditions required for its coherent implementation, thus effectively contributing to the construction of an autonomous school community committed to the transformation of the social-cultural reality in which it is located.
Keywords: Formação continuada; Educação popular; Alfabetização; Participação; Emancipação; Diferença; Continuing education; Popular education; Literacy; Participation; Emancipation; Difference; ACCNPQ::Ciências Humanas::Educação